Rationalising the business structure of contemporary Buddhist organisations in Malaysia: a case study of five Buddhist charities - Lee, Yok Fee; Low, Kok On (Penerbit Universiti Sains Malaysia, 2023)
Many contemporary Buddhist organisations have registered in Malaysia since the early 21st century. This article aims to analyse the issues of rationalisation in terms of the structure of organisational and the business concepts of five contemporary Buddhist organisations. In-depth interview, telephone interview, and observation were the methods used to gather qualitative data from the informants and the websites of the selected organisations. Weber’s concepts of rationalisation were employed to analyse data collected from the field as well as the secondary data. In terms of the organisational structure, our analysis revealed that two out of five selected Buddhist organisations, namely Kechara and Tzu Chi, are highly structured and formalised. In addition, their bureaucracy is in line with Weber’s rationalisation model that emphasised calculability, predictability, control, and capitalism. In terms of business, two out of five selected Buddhist organisations, namely the Buddha’s Light International Association and the Nalanda Buddhist Society do not participate in business. In other words, these two organisations showed that the Buddhist’s norm and values do not rationalise the believers into accumulating wealth as their goal and then creating the spirit of capitalism. However, the Kechara, Tzu Chi, and Buddhist Business Network do actively participate in business activities to generate their own income. The elements of calculability, predictability, control, and capitalism are significant in all the three organisations’ business involvement too. Overall, this study has indirectly highlighted the similarities and differences of the five selected contemporary Buddhist organisations in Malaysia with respect to their structure of organisation and business involvement based on Weber’s concepts of rationalisation.